2019
DOI: 10.1021/acscentsci.8b00588
|View full text |Cite
|
Sign up to set email alerts
|

Oligomannose Glycopeptide Conjugates Elicit Antibodies Targeting the Glycan Core Rather than Its Extremities

Abstract: Up to ∼20% of HIV-infected individuals eventually develop broadly neutralizing antibodies (bnAbs), and many of these antibodies (∼40%) target a region of dense high-mannose glycosylation on gp120 of the HIV envelope protein, known as the “high-mannose patch” (HMP). Thus, there have been numerous attempts to develop glycoconjugate vaccine immunogens that structurally mimic the HMP and might elicit bnAbs targeting this conserved neutralization epitope. Herein, we report on the immunogenicity of glycopeptides, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 75 publications
6
50
0
Order By: Relevance
“…In contrast to our observations with the conjugates, in vitro assays with SOSIP trimers showed no trimming of glycans comprising the oligomannose patch, demonstrating that these oligomannose-type glycans, unlike those presented on glycoconjugates, are protected from mannosidase trimming, presumably because of their more dense packing on Env. Our results along with those of Nguyen et al 20 allow for an explanation of why immunizing rabbits with recombinant yeast expressing an abundance of oligomannose 16,46,47 or prolonged repetitive immunization of macaques with a recombinant gp140 trimer imparted with an intact oligomannose patch 48 might yield mannose-specific antibodies with at least some affinity for full-sized oligomannose, whereas immunizing with oligomannose or oligomannose-like glycans displayed on virus-like particles 11,49 , oligomannosidic glycoconjugates 10,12,13,15,17 or glycopeptides presenting oligomannose 20,28 has resulted mostly in the elicitation of antibodies that are generally less capable of binding oligomannose.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In contrast to our observations with the conjugates, in vitro assays with SOSIP trimers showed no trimming of glycans comprising the oligomannose patch, demonstrating that these oligomannose-type glycans, unlike those presented on glycoconjugates, are protected from mannosidase trimming, presumably because of their more dense packing on Env. Our results along with those of Nguyen et al 20 allow for an explanation of why immunizing rabbits with recombinant yeast expressing an abundance of oligomannose 16,46,47 or prolonged repetitive immunization of macaques with a recombinant gp140 trimer imparted with an intact oligomannose patch 48 might yield mannose-specific antibodies with at least some affinity for full-sized oligomannose, whereas immunizing with oligomannose or oligomannose-like glycans displayed on virus-like particles 11,49 , oligomannosidic glycoconjugates 10,12,13,15,17 or glycopeptides presenting oligomannose 20,28 has resulted mostly in the elicitation of antibodies that are generally less capable of binding oligomannose.…”
Section: Discussionsupporting
confidence: 57%
“…This notion was raised in a recent report 20 describing an attempt to elicit 2G12-like bnAbs in rabbits using multivalently displayed glycopeptide immunogens. The report showed that the resulting antibodies were largely specific for the proximal glycan core rather than the distally located tips of the target glycans 20 . It was suggested that this outcome might be the result of the activity of a mannosidase in (rabbit) serum that trims full-sized oligomannose on administered glycoproteins [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…In the recent report suggesting that serum mannosidases might be impeding the elicitation of oligomannose-specific bnAbs 20 , the Man 9 -peptide conjugate designed in the study was retrieved for mass spectrometric analysis after incubation in rabbit serum. Results showed that>90% of the Man 9 was trimmed to Man 6 within 24 h. In line with the results of that report, we found here using an ELISA format that PGT128 binding to both the BSA-conjugated (NIT82B) and the CRM 197 -conjugate glycoside (NIT211) is substantially diminished after a 24 h-incubation in situ with different mammalian sera relative to buffer control (Fig.…”
Section: Serum Mannosidase Trims the Crm 197 -Conjugated Glycoside Inmentioning
confidence: 99%
“…One possible alternate explanation for the prevalence of antibodies that are specific for oligomannose substructures-rather than full-sized oligomannose-could be that the elicited antibodies reflect a heretofore unappreciated occurrence in vivo: enzymatic trimming of the administered glycosides. This notion was raised in a recent report 20 describing an attempt to elicit 2G12-like bnAbs in rabbits using multivalently displayed glycopeptide immunogens. The report showed that the resulting antibodies were largely specific for the proximal glycan core rather than the distally located tips of the target glycans 20 .…”
mentioning
confidence: 99%
See 1 more Smart Citation